Retrospective survival analysis in patients with metastatic pancreatic ductal adenocarcinoma with insulin-treated type 2 diabetes mellitus. Issue 6 (December 2021) - Pretta, Andrea; Ziranu, Pina; Puzzoni, Marco; Lai, Eleonora; Orsi, Giulia; Liscia, Nicole; Molinaro, Eleonora; Mariani, Stefano; Riggi, Laura; Rovesti, Giulia; Dubois, Marco; Migliari, Marco; et al.
Introduction: The association between pancreatic ductal adenocarcinoma (PDAC) and type 2 diabetes mellitus (DM2) has long been evaluated and the role of antidiabetic medications such as metformin has also been investigated. The objective of this study was to examine the association between insulin use and overall survival (OS) in patients with advanced PDAC and DM2. Methods: We retrospectively collected data from 164 patients, including an exploratory cohort of 96 patients from Medical Oncology Unit, University Hospital and University of Cagliari, Italy, and a validation cohort of 68 patients from Medical Oncology of Modena University Hospital. Patients had metastatic disease and received a first-line gemcitabine-based chemotherapy and, subsequently, a second-line fluoropyrimidines-based chemotherapy. We performed univariate analysis to evaluate correlation between long-term diabetes and overall survival. Then we performed multivariate analysis, adjusting for sex, metastatic sites, Eastern Cooperative Oncology Group Performance Status, Ca19.9 levels, N/L ratio, and lactate dehydrogenase levels at diagnosis, to confirm the independence of the variable. Results: In the exploratory cohort, DM2 was significantly associated with higher median OS at univariate analysis (16 vs 10 months; p = 0.004). This result was confirmed by validation cohort (11 months vs 6 months; p = 0.01). In multivariate analysis, insulin-treated patients compared with non diabetic patients showed a significantly increased survival of 4.6 months ( p = 0.03). Conclusions: Patients with insulin-treated metastatic PDAC showed better OS than non diabetic patients, as demonstrated by both cohorts. The correlation between OS and insulin-treated DM2 should be investigated further through a prospective clinical trial.